Antioxidant and Protective Effects of Oleaster Oil Against Silica Nanoparticle-Induced Oxidative Stress and Organ Toxicity in Rats - Malika Hamdiken; Amina Bouzitouna; Manel Hami; Yousra Seridi; Nedjoud Grara; Hayette Ayed; Abdelghani Boudjahem; Rabah Zebsa; Prospero Di Pierro; Andrea Balivo; Alessandro Genovese (Applied Sciences)
Nanoparticles have found widespread application in a variety of fields, despite growing worry about their possible hazardous effects on both the environment and human health. In recent years, research efforts have focused on plants and vegetable oils, which have been identified as abundant sources of many bioactive compounds. Many of these substances are known to participate in antioxidant processes. As a result, the current study was designed to investigate the antioxidant and protective properties of oleaster oil against cytotoxicity and oxidative stress induced by silica nanoparticles (SiNPs) in albino Wistar rats. Forty male rats were randomly assigned to four equally sized cohorts: a control group, SiNP-treated group (at a dose of 50 mg/kg), SiNP-treated group supplemented with oleaster oil (at a dose of 2 mL/kg), and those receiving only 2 mL/kg of oleaster oil. The findings demonstrated that SiNPs initiated an oxidative stress environment, as evidenced by higher lipid peroxidation levels and changes in antioxidant defense mechanisms. Antioxidant enzymes were significantly reduced, including glutathione levels between the control and SiNP-exposure treatments (36.01%, 36.59%, 60%), glutathione-S-transferase (29.74%, 29.90%, 13.49%), catalase (24.14%, 28.19%, 30.85%), and tissue superoxide dismutase (11.90%, 37.78%, 37.79%) in the liver, kidney, and heart, respectively. Furthermore, histological investigations revealed significant liver, kidney, and heart damage, as indicated by pathological alterations such as vascular dilatation and congestion, inflammatory cellular infiltration, and hepatocellular dysfunction. Encouragingly, the administration of oleaster oil significantly ameliorated a majority of these detrimental effects. These data suggest a potential protective effect of oleaster oil against the adverse histological effects induced by SiNP injection.